2019
DOI: 10.1108/jima-10-2018-0187
|View full text |Cite
|
Sign up to set email alerts
|

Halal brand personality and brand loyalty among millennial modest fashion consumers in Malaysia

Abstract: Purpose The growing competition in Malaysia’s modest fashion industry has proven to be the main challenge for the business to stay relevant in the market. Based on this reason, it is vital for marketers to create a differentiation in their brands to attract more customers. One of the ways to create this differentiation is by establishing brand personality. Brand personality does not only differentiate from one product to another but is also a common strategy used by marketers to create competitive advantage fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 58 publications
3
38
1
3
Order By: Relevance
“…Hence, looking back at the concept of their nature (fitrah), it is recommended for Muslims to purchase products that are halal certified. In this view, service producers have to ensure that the products that they sell are free from any forbidden (haram) ingredients, (Zainudin, Hasan & Othman, 2019). Furthermore, it is very crucial for service providers to ensure that the resources and the distribution channels are pure and free from illegal components that might jeopardize the purity of the products and services, (Shaari & Arifin, 2010).…”
Section: Puritymentioning
confidence: 99%
“…Hence, looking back at the concept of their nature (fitrah), it is recommended for Muslims to purchase products that are halal certified. In this view, service producers have to ensure that the products that they sell are free from any forbidden (haram) ingredients, (Zainudin, Hasan & Othman, 2019). Furthermore, it is very crucial for service providers to ensure that the resources and the distribution channels are pure and free from illegal components that might jeopardize the purity of the products and services, (Shaari & Arifin, 2010).…”
Section: Puritymentioning
confidence: 99%
“…A study by Abdul Kadir (2011) in Malaysia demonstrated that the Millennials did not display a sense of guilt while eating in a non-Halal caf e. Realizing this, only few researches have examined Millennial consumer group in the context of Halal business (e.g. Ishak et al, 2019;Marmaya et al, 2019;Osman and Aziz, 2018;Yusof et al, 2019;Zainudin et al, 2019), even though insightful knowledge could be generated for Halal business development. In light of this research gap, this study aims to examine Halal food purchasing behavior of Muslim Millennials in a Muslim-majority country by considering habit and intention as the primary determinants.…”
Section: Introductionmentioning
confidence: 99%
“…However, in-depth literature review within this area has outlined diverging notions. From one end, purchasing behaviours were assessed through exploring the cognitive standpoint, constituting variables of uniqueness, value consciousness (Henninger et al, 2018), cultural and religion endorsements (Zainudin et al, 2019), attitude and subjective norms (Nash, 2019). From the other end, marketing and social dimensions were appraised, with accounts for content sharing (Natalia, 2019), social influencers (Sanmiguel et al, 2018), online communities (Helal, 2019) and collaborative consumptions (Iran and Schrader, 2017).…”
Section: Introductionmentioning
confidence: 99%